Quality assessment of pharmaceutical care to patients with headaches using the simulated patient method: drug recommendations and pharmaceutical counseling - O. V. Reshetko; A. I. Gris (Izdatelstvo OKI, 2023)
Relevance. Headaches are one of the most important health problems both in Russia and around the world, as well as one of the most common reasons for self-treatment in a pharmacy due to the availability of over-the-counter drugs. Pharmaceutical workers play an important role in the control of self-medication, and the rationality of drug recommendations determines the quality of pharmaceutical care.Aim. To assess the rationality of drug recommendations for a patient with a headache and pharmaceutical drug counseling using the simulated patient method.Materials and methods. Trained simulated patients (women aged 20, 40 and 58 years) visited a total of 101 pharmacies. The dialogue was recorded on a voice recorder, all the features of the interaction were additionally recorded aﬅer the visit. Special forms were ﬁlled out based on the information received. The data was processed using Microsoﬅ Excel 2010 and STATISTIKA 10.0.Results. There was a high frequency of spontaneous recommendations without preliminary questions (66.3%), recommendations (14.9%) and dispensing of prescription drugs (5.0%), frequent recommendations of combined drugs (91.0%). Trade name Pentalgin (46.5%) and trade name Nurofen (42.6%), INN Ibuprofen (47.5%) were the most recommended. Combination analgesics were purchased in most of the visits (72.0%), information on the duration of use of the drug and the need to visit a doctor was never provided.Conclusion. Pharmacists' recommendations are in most cases irrational, focused on the drug as a product and sometimes unsafe, and counseling is practically non-existent. Improving the quality of pharmaceutical care at this stage should include the development of standards for drug recommendations and adequate counseling.